Residential electricity consumption and adaptation to climate change by Colombian households - Shaun D. McRae (Inter-American Development Bank (IDB), 2023)
This paper provides the first empirical estimates of the relationship between temperatures and household electricity consumption in Colombia, using electricity billing and weather data from 2010 to 2019. I find that higher temperatures (or higher values of the heat index) increase electricity consumption, with the largest effects observed for high-income households in regions with hot climates. However, I show that there has been partial convergence between low- and highincome households, with the effect of temperature on electricity consumption in lower-income neighborhoods more than doubling between 2011 and 2019. These results align with survey evidence of increased air conditioning adoption. Nevertheless, further growth in air conditioning adoption and use is required to alleviate the health effects of more frequent and severe heatwaves due to climate change.
Keywords: L94; O13; Q41; Q54; 330; Electricity consumption; Climate change; Adaptation; Air conditioning